IDENTIFICATION AND PATHOLOGY OF STRONGYLUS SPECIES IN NATURALLY INFECTED MULES.‎ - M.Al-Saqur, I.; H.Khamas, W.; N.Al-Taee ‎, S .; ‎ Al-Grabawi‎, M. (The Iraqi Journal of Veterinary Medicine, 1987)
Naturally infected large intestine of 16 mules were collected during one year period. All three species of Strongylus were identified: S.vulgaris, S.equinus and S.edentatus. Specimens were processed for standard histological examination. The effect of the parasite on the wall of the intestine ‘included the _ surface epithelium, glandular tissue, muscularis mucosa and part of the submucosa. Changes on the intestinal wall were observed at the site of the parasitic attachement, which included oedema, cellular infilteration with congestion and haemorrhages.